Implementing Integrated Project Based Learning to Enhance Students’ Writing Skill - Ekawati, Wahyu (ELLITE, 2018)
Writing in English is important for vocational high school (SMK) students toprepare their future career so that they can compete with other job seekers bothin Indonesia and other countries. However, the students find that writing isdifficult to learn due to some cases: (1) they are less interested in it because it isnot correlated with their major, (2) the limited time availability (3) the teachinglearning process is less meaningful, and (4) they are lack of feedback due to thebig number of students in one class. To overcome this problem, it is advisableto apply what so called integrated project based learning (PBL) by integratingwriting to recount the project dealing with the students’ major. This paperdescribes how the integrated PBL can enhance the students’ writing skill throughtwo main stages: (1) preparation stage. It is embodying grouping, determiningthe project work, determining the schedule, and learning the content as wellas how to write a recount text in the classroom. (2) individual writing activitywhich covers (a) free writing; (b) drafting; (c) evaluating (peer reviewing andteacher learner conference); (d) revising; (e) post writing; (f) publishing in asocial media; and (g) responding the social media reader’s comment.